Comparing the Effectiveness of Emotionally Focused Couple Therapy and Systemic Couple Therapy on Executive Functions and Negative Meta-Emotion in Couples with Marital Conflicts - Sajedi, Haleh; Sadati, Seyedeh Zahra (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of Emotionally Focused Couple Therapy (EFT) and Systemic Couple Therapy on executive functions and negative meta-emotion among couples experiencing marital conflicts. Methods and Materials: This study employed a quasi-experimental design with pretest, posttest, and three-month follow-up assessments alongside a control group. The statistical population consisted of married couples with marital conflict who referred to counseling centers in Tehran in 2025. Following screening and informed consent, 45 couples were selected using purposive sampling and randomly assigned to three groups: EFT (15 couples), Systemic Couple Therapy (15 couples), and a control group (15 couples). The EFT group received eight weekly 90-minute sessions based on the Greenberg model, while the systemic group received eight weekly 90-minute sessions grounded in Minuchin’s structural approach; the control group received no intervention. Data were collected using the Marital Conflict Questionnaire, the Barkley Deficits in Executive Functioning Scale, and the Meta-Emotion Questionnaire (negative meta-emotion dimension). Data were analyzed using repeated-measures multivariate analysis of variance and Bonferroni post hoc tests in SPSS version 26. Findings: Results of the multivariate mixed ANOVA indicated significant main effects of time and significant time × group interactions for both executive functions and negative meta-emotion (p < 0.001). Both EFT and Systemic Couple Therapy significantly improved executive functioning and reduced negative meta-emotion compared with the control group at posttest and follow-up (p < 0.05). However, EFT demonstrated significantly greater improvements than Systemic Couple Therapy in enhancing executive functions and reducing negative meta-emotion at posttest and follow-up (p < 0.05). Treatment effects remained stable at the three-month follow-up. Conclusion: Both Emotionally Focused Couple Therapy and Systemic Couple Therapy are effective interventions for improving executive functioning and reducing negative meta-emotion in couples with marital conflict; however, EFT appears to produce stronger and more sustained cognitive and meta-emotional outcomes.